Additions to the euophryine jumping spider fauna (Araneae: Salticidae) of Australia - Richardson, Barry J. (Zootaxa, 2022)
Previously unknown species in the genera Barraina Richardson, 2013 and Frewena Richardson, 2013, the undescribed female of Prostheclina boreoaitha Richardson and Żabka, 2007 and a new synonym of Servaea incana (Karsch 1878), namely Cytaea morrisoni Dunn, 1951 n. syn., are described here. The suggestion that Servaea vestita (Koch, L., 1879) be reinstated from the synonymy of S. incana is reviewed and, on the basis of morphological and molecular data, not accepted. The new species are: Barraina abbedar n. sp., Barraina banyabba n. sp., Barraina melanoros n. sp., Barraina occidentalis n. sp., Barraina pilata n. sp. and Frewena terraregina n. sp..